2015
DOI: 10.1002/anie.201500109
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Tri‐ and Tetranuclear Titanacycles through Decamethyltitanocene‐Mediated Intermolecular C–C Coupling of Dinitriles

Abstract: The reactions of [Cp*2 Ti(η(2) -Me3 SiC2 SiMe3 )] (Cp*=η(5) -pentamethylcyclopentadienyl) with various dicyano compounds were investigated. Nitrile-nitrile CC couplings result in multinuclear complexes owing to the bifunctionality of the substrates. Applying 1,3- or 1,4-dicyanobenzene led to tri- and tetranuclear complexes of the rare 1-metalla-2,5-diaza-cyclopenta-2,4-dienes. These are potential catalysts and were tested in the ring-opening polymerization of ε-caprolactone. The reaction with adiponitrile as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 35 publications
4
40
0
Order By: Relevance
“…This supports spontaneously C-C coupling reactions of 1,3-or 1,4dicyanobenzene, [12] adiponitrile, [12] 2,6-dicyanopyridine [13] or pyrazine [9,14] without or of quinoxalines [15] with C-H bond activation reactions and enable for instance the formation of the trinuclear complexes IV and V (Scheme 2). This supports spontaneously C-C coupling reactions of 1,3-or 1,4dicyanobenzene, [12] adiponitrile, [12] 2,6-dicyanopyridine [13] or pyrazine [9,14] without or of quinoxalines [15] with C-H bond activation reactions and enable for instance the formation of the trinuclear complexes IV and V (Scheme 2).…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…This supports spontaneously C-C coupling reactions of 1,3-or 1,4dicyanobenzene, [12] adiponitrile, [12] 2,6-dicyanopyridine [13] or pyrazine [9,14] without or of quinoxalines [15] with C-H bond activation reactions and enable for instance the formation of the trinuclear complexes IV and V (Scheme 2). This supports spontaneously C-C coupling reactions of 1,3-or 1,4dicyanobenzene, [12] adiponitrile, [12] 2,6-dicyanopyridine [13] or pyrazine [9,14] without or of quinoxalines [15] with C-H bond activation reactions and enable for instance the formation of the trinuclear complexes IV and V (Scheme 2).…”
Section: Introductionsupporting
confidence: 70%
“…Using imidazole 5, 4,5-dimethylimidazole 6, benzimidazole 7 and 5,6-dimethylbenzimidazole 8 with the metallocene precursors [Cp 2 Ti(η 2 -C 2 (SiMe 3 ) 2 )] 1 and [Cp 2 Zr(py)(η 2 -C 2 (SiMe 3 ) 2 )] 2 resulted in the formation of the molecular rectangles 10-15. Reactions with zirconium were performed in n-hexane (12) or in a mixture of toluene/n-hexane (13) at 60°C without stirring and nearly black to violet crystals suitable for X-ray diffraction were obtained in moderate to good yields of 32-78 %. Reactions with zirconium were performed in n-hexane (12) or in a mixture of toluene/n-hexane (13) at 60°C without stirring and nearly black to violet crystals suitable for X-ray diffraction were obtained in moderate to good yields of 32-78 %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later by C‐C coupling reactions of benzodinitriles like 1,3‐ and 1,4‐dicyanobenzene by using Cp* 2 Ti(η 2 ‐btmsa) depending on the substitution of the cyano groups tri‐ or tetranuclear complex were obtained (Scheme ) …”
Section: Self‐assembly Reactions To Multinuclear Complexesmentioning
confidence: 99%
“…These were established by C−C couplings of aryl nitriles at [Cp* 2 M] (M=Ti, Zr) and isolated in high yields . This method could also be extended to dicyanobenzenes, thus forming tri‐ and tetranuclear compounds . Exploring the reactivity of Cp* 2 M(N=C(Ph)−C(Ph)=N) (M=Ti, Zr) towards H 2 , CO 2 or CH 3 −C≡N showed that the C−C bond of the five‐membered metallacycles was easily cleaved .…”
Section: Introductionmentioning
confidence: 99%